2007
DOI: 10.1136/thx.2006.061630
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal smoking with increased infant oxidative stress at 3 months of age

Abstract: Background: Cigarette smoke is a major source of free radicals and oxidative stress. With a significant proportion of women still smoking during pregnancy, this common and avoidable exposure has the potential to influence infant oxidative status, which is implicated in the increased propensity for airway inflammation and asthma. The aim of this study was to examine the effects of maternal smoking on markers of infant oxidative stress. Methods: The level of oxidative stress (using urinary F 2 -isoprostanes as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 21 publications
0
53
1
Order By: Relevance
“…It has been shown that maternal smoking is associated with increased levels of oxidative stress markers in the mother and offspring [37,38]. There is also convincing in vivo and in vitro evidence suggesting that exposure to nicotine results in oxidative stress in fetal, neonatal and adult tissues [38,39].…”
Section: Nicotine and Oxidant/antioxidant Statusmentioning
confidence: 91%
“…It has been shown that maternal smoking is associated with increased levels of oxidative stress markers in the mother and offspring [37,38]. There is also convincing in vivo and in vitro evidence suggesting that exposure to nicotine results in oxidative stress in fetal, neonatal and adult tissues [38,39].…”
Section: Nicotine and Oxidant/antioxidant Statusmentioning
confidence: 91%
“…14,[27][28][29][30][31] The study included almost all 11-to 12-year-olds in these 3 municipalities as school attendance is mandatory in Sweden, virtually eliminating selection bias. Through use of an extensive questionnaire, the study cohort was well characterized.…”
Section: Methodologic Aspectsmentioning
confidence: 99%
“…33 Prenatal smoke exposure affects exhaled nitric oxide, 29 increases levels of F2-isoprostanes in infants, 34 and also increases T-helper type 2 cell responses in neonates. 28 Thus, it seems that although birth weight mainly affects lung function, prenatal and later smoke exposure has immunologic effects associated with the development of asthma. We therefore postulate that airway inflammation from prenatal smoking in an underdeveloped lung owing to intrauterine growth impairment could explain the interaction seen in our study.…”
Section: Independent Effects Of Lbw and Prenatal Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking results in increased morbidity and mortality from cancers, cardiovascular and pulmonary disease in the mother, and has been implicated in the etiology of abruption placenta, placenta previa, spontaneous abortion, premature delivery, and stillbirth (Meyer, Jonas, & Tonascia, 1976;Naeye, 1979;Ness et al, 1999;Walsh, 1994). Recent findings have confirmed significant immunological effects of smoking on the fetus, resulting in higher rates of respiratory infections, asthma (Noakes, Hale, Thomas, & Devadason, 2006) and cancer (Sheung & Zelikoff, 2006). Results from a study based on 9,000 pregnancies found that maternal smoking also reduced the chances of conceiving a male child, and may have prevented male embryos from implanting in the womb, causing miscarriages (Woolfe, 2007).…”
Section: Chapter One Background Researchmentioning
confidence: 87%